Change and execute how to transform and design your business for sustainable success - Phillips, Kevin E. (Productivity Press, 2021)
The business environment is changing at a faster rate than ever, with transformational shifts taking place in every industry and market in the world. These changes create increased risks for companies that remain complacent. However, they also generate opportunity for businesses willing to adapt and evolve. The key is transforming your organization to meet the demands of tomorrow. Change and Execute: How to Transform and Design Your Business for Sustained Success has been written to help you do just that. This book provides strategic insights, solutions, and direction that will empower you to improve your organization by providing definitive actions that will transform potential into productivity to generate sustained success. You are encouraged to use this book to transform your organization and take it to the next level! Features: Shares 10 changes that will have an enormous impact on the future of business over the next 10 years Highlights the importance of maximizing the value companies deliver to customers Shares the increased threats that are now present due to global competition Includes a fascinating case study on how the Golden State Warriors revolutionized the NBA and effectively draws parallels to how business has evolved in the 21st century Explains how changes in the workplace have shifted the perspective of the "traditional" employee Provides new characteristics and traits leaders need to be successful Examines how policies, processes, procedures, and performance have changed in the workplace Discusses actions companies must take to generate sustained results Describes the risks that are present when you are resistant to change